Malaria Situation in The South Kalimantan Province, 2010–2018 - M Rasyid Ridha; Kasman Kasman; Evi Liani; Liestiana Indriati (Universitas Airlangga, 2021)
Background: Malaria has caused high morbidity and mortality rates and has decreased the productivity of human resources and national development. Malaria is endemic in several districts in South Kalimantan. Purpose: This study aims to describe the malaria situation in South Kalimantan by examining the malaria cases, Case Fatality Rate (CFR), Annual Parasite Incidence (API), and Slide Parasite Rate (SPR) in the South Kalimantan Province during the period of 2010–2018. Method: This research was a descriptive study with the South Kalimantan population, who were at risk of getting malaria. This study adopted a total participation technique and included all the cases of malaria recorded in the electronic- Surveillance Information System of Malaria (e-SISMAL) data of South Kalimantan province in the period 2010–2018. The study used secondary data from the South Kalimantan Provincial Health Office during 2010–2018. The data included the number of malaria cases, morbidity, and the mortality rate of malaria. The data collected was analyzed using CFR, API, and the SPR formulae. Results: The number of malaria cases in South Kalimantan from 2010 to 2018 fluctuated. The highest number of malaria cases occurred in 2011, while a decreasing trend was observed up to 2018. At the same time, the number of deaths during 2012–2018 increased. The death rate from 2010–2018 decreased in South Kalimantan. Conclusion: The number of cases as well as deaths caused due to malaria in South Kalimantan continues to decrease. By 2025, all districts in South Kalimantan could be free from malaria.